Regional Integration and National Disintegration in the Post-Arab Spring Middle East. - El-Anis, Imad H. (Cambridge Scholars Publishing, 2016)
This edited collection explores the processes of change currently shaping the Middle East in the post-Arab Spring context. The national and transnational challenges that have emerged since the uprisings in 2011 - particularly the increase in extremism, and the emergence and intensification of civil wars - have garnered significant attention in both media coverage and academic research. However, simultaneous (and far older) processes of regional integration - varying in form from free trade agreements like the Greater Arab Free Trade Area to economic and political unions like the Gulf Cooperati.